THE ROLE OF HUMAN RESOURCE MANAGEMENT IN ENHANCING EMPLOYEE LOYALTY: A CASE STUDY AT YAYASAN BAITUL INSAN KHOIR - Ummi Kultsum (BAIK Publishers, 2026)
This study examines the role of Human Resource Management (HRM) in enhancing employee loyalty at Yayasan Baitul Insan Khoir. The research adopts a qualitative approach using semi-structured interviews and field observations involving foundation leaders, administrative staff, and program officers. Data were analyzed through thematic analysis to identify patterns related to HRM practices, employee loyalty, influencing factors, and organizational challenges. The findings reveal that HRM within the foundation is predominantly operational, focusing on administrative functions such as recruitment, attendance, and task allocation, while strategic HR components particularly career development, performance appraisal, and talent management remain underdeveloped. Employee loyalty is largely affective in nature, driven by emotional attachment to the organization’s social mission, value alignment, and supportive interpersonal relationships. However, long-term loyalty is weakened by limited career pathways, workload imbalance, and financial constraints. Organizational support and shared values emerge as the most influential factors sustaining short-term commitment, whereas the absence of structured career development systems and formal performance evaluation significantly reduces employees’ intention to remain. The study also identifies key organizational barriers, including limited resources, role overlap, lack of recognition mechanisms, and the positioning of HRM as an administrative rather than strategic function. The research concludes that intrinsic motivation alone is insufficient to sustain long-term employee loyalty. Strategic HRM practices integrating career development, continuous training, performance management, and organizational support are essential for strengthening employee commitment and organizational sustainability. This study contributes to HRM literature by providing empirical insights from a nonprofit context and offers practical recommendations for enhancing employee loyalty through strategic HRM implementation.